Komunikasi Visual pada Desain Produk Clothing Line - Rifqi Aufa Ramadhana; Anne Ratnasari (Bandung Conference Series: Communication Management, 2023)
Abstract. Popculine as a Clothing line brand really thinks about their product design concept. Popculine's product design has the characteristic that the product is black and white and includes quotes or words that describe something that is currently being discussed. This study aims to find out 1) the implementation of Popculine's product design elements, 2) the reasons for choosing black and white colors and including quotes on each product owned by the Popculine fashion brand, and 3) Popculine's obstacles in making its product designs and efforts to overcome them. This study uses a qualitative research method with a case study approach, the researcher wants to find out more about how visual communication is in the product design of the Popculine fashion brand. The data collection techniques for this research are observation, interviews, documentation, and literature study. The research subjects were Popculine as key informants and supporting informants, UNISBA communication science lecturers and a graphic designer. Researchers used data analysis techniques such as data reduction, data presentation, and drawing conclusions. In testing the validity of the data, researchers used data triangulation. The results of this study 1) the implementation of the Popculine product design is identifying problems, seeking initial ideas, making design improvements, developing prototypes, and evaluating design prototypes. 2) Popculine's obstacles in making product designs include difficult vendor selection, and searching for written references on Popculine product designs. Efforts to overcome this are strict supervision in the production process, and being up to date with trends. 3) The reason for choosing black and white colors and including quotes on Popculine products is to make it easier to arrange displays at Popculine stores, distinguish Popculine from other brands, and so that Popculine has a clear path in making its product designs. Abstrak. Popculine sebagai sebuah merek Clothing line sangat memikirkan konsep desain produk mereka. Desain produk Popculine memiliki ciri yaitu produknya berwarna hitam putih dan mencantumkan quotes atau kata-kata yang menggambarkan sesuatu yang sedang hangat dibicarakan. Penelitian ini bertujuan untuk mengetahui 1) implementasi elemen-elemen desain produk Popculine, 2) alasan pemilihan warna hitam dan putih serta mencantumkan quotes pada setiap produk yang dimiliki oleh merek fesyen Popculine, dan 3) hambatan Popculine dalam membuat desain produknya serta upaya mengatasinya. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus, peneliti ingin mencari tahu lebih dalam bagaimana komunikasi visual pada desain produk merek fesyen Popculine. Teknik pengumpulan data penelitian ini adalah, observasi, wawancara, dokumentasi, dan studi kepustakaan. Subjek penelitan yaitu pihak Popculine sebagai key informan dan informan pendukung yaitu dosen ilmu komunikasi UNISBA dan seorang desainer grafis. Peneliti menggunakan teknik analisis data seperti, reduksi data, penyajian data, dan penarikan kesimpulan. Dalam menguji keabsahan data, peneliti menggunakan triangulasi data. Hasil dari penelitian ini 1) implementasi desain produk Popculine adalah identifikasi masalah, mencari ide awal, melakukan perbaikan desain, mengembangkan prototipe, dan melakukan evaluasi prototipe desain. 2) Hambatan Popculine dalam membuat desain produk meliputi pemilihan vendor yang sulit, dan pencarian referensi tulisan pada desain produk Popculine. Upaya mengatasinya adalah pengawasan yang ketat dalam proses produksi, dan up to date terhadap trend. 3) Alasan pemilihan warna hitam putih dan pencantuman quotes pada produk Popculine adalah untuk memudahkan penyusunan display di toko Popculine, membedakan Popculine dengan merek lain, dan agar Popculine memiliki jalur yang jelas dalam membuat desain produknya.